ISSUES OF ACOUSTICS AND PERFORMANCE SKILLS IN DUTOR DRUM (Neo Scientific Peer Reviewed Journal, 2023)
This article discusses the history of the origin of ancient Uzbek music and the acoustics and performance skills of the Dutor instrument.